Organização do arquivo escolar do Colégio de Aplicação da UFS: preservação do patrimônio histórico e educacional e potencialidades para a escrita da história da educação - Almeida, Anne Emilie Souza de (2023)
Taking as object the permanent documentation of the School of Application of Sergipe’s Federal University, this research has as general objective to propose the intellectual organization of the permanent documents of the School of Application of Sergipe’s Federal University, guarded at the Center for Research, Documentation and Memory of UFS’ School of Application, highlighting its value as educational historical heritage and its potential for the production of research sources. From this general objective, the following specific objectives were defined: to discuss the relevance of school documentation as educational historical heritage within the scope of Educational History; understand important milestones in the history of UFS’ School of Application; apply archival principles and techniques in the documents organization process; create a research tool that guarantees rationalized access to documents; and to relate the process of organizing school documents with an increase in the production of knowledge in the field of Educational History. It was defined as a hypothesis that the organization of the accumulated documental mass of an educational institution, following the methods and techniques of Archivology and relating them to the concept of educational historical heritage, contributes to an organizational logic of the collections as well as the analysis of the documents as potential sources for research in Educational History. The time frame of this research begins in 1959, when the institution was founded and the documentary production began; and, considering the “vital cycle of documents” and the institution’s age, 1998 was defined as the final milestone. Among others, the concepts or notions considered and/or discussed were educational historical heritage (MENEZES, 2011; MOGARRO, 2005), archive (BELLOTTO, 2006), school archive (LUZ, 2013) and memory center (CAMARGO; GOULART, 2019). For the proposal of organization, the Classification Plan of the Permanent Documentation of the School of Application and the Inventory of the Permanent Collection of UFS’ School of Application were constructed. The documentation presents, among others, information that may give rise to problematization regarding educational intellectuals, educational practices, school subjects, institution’s history, profession and teaching practices, student career. Therefore, the work of organizing the accumulated document mass and the proposal of a classification plan, in addition to the construction of the inventory linked to the reflections of school documents in the dimension of educational historical heritage, contribute to highlighting potentialities for the writing of Educational History and equally for the preservation of institutional memory and agents of educational action